The Meaning and Limitations of a Notary's Obligation in Safeguarding the Interests of the Parties in Legal Acts from the Perspective of Legal Certainty - Rachman, Isnilah Nur; Widhiyanti, Hanif Nur; Wisnuwardhani, Diah Aju (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to the meaning and limitations of a notary's obligation to “safeguard the interests of the parties involved in legal acts” as stipulated in Article 16 paragraph (1) letter a of the Indonesian Notary Position Act. This provision raises ambiguity or lack of clarity due to the insufficient explanation in the law, particularly regarding the phrase